'Seaweed appearance' in squamous cell carcinoma of the penis: A new dermoscopic finding - Wei Zhang; Lingxi Gu; Jianglong Feng; Hui Fan; Hongguang Lu (Wiley, 2023)
Abstract Squamous cell carcinoma of the penis is an uncommon cancer. Vascular feature on dermoscopy is common in all forms of invasive squamous cell carcinoma, and the presence of the specific vascular features is often used to aid diagnosis. Here, we reported a new dermoscopic finding-seaweed‐like vascular pattern in squamous cell carcinoma of the penis.